The complete mitogenome of the Mountain chicken frog, Leptodactylus fallax - White, Nina F. D. (Mitochondrial DNA B Resour, 2021)
The mountain chicken frog (Leptodactylus fallax) is a critically endangered frog native to the Caribbean islands of Dominica and Montserrat. Over the past 25 years their populations have declined by over 85%, largely due to a chytridiomycosis outbreak that nearly wiped out the Montserratian population. Within the context of developing tools that can aid in the conservation of the mountain chicken frog, we assembled its complete mitochondrial genome, contributing the first complete mitogenome of the genus Leptodactylus (Genbank Accession number MW260634). The circular genome is 18,669 bp long and contains 37 genes. A phylogenetic analysis reveals that L. fallax forms a clade with Leptodactylus melanonotus, highlighting the close relationship of Leptodactylus spp. relative to other species from the superfamily Hyloidea included in the analysis.